Exploring Genetic Variation in Brassica rapa for Improved Yield and Fatty Acid Profiles (Plant Bulletin, 2023)
Brassica rapa is one of the most widely cultivated oilseed crops and is known for a variety of benefits across the globe. Brassica rapa is one of the key Brassica species. Together with significant oil concentrations, it is distinguished by a high concentration of macro and micronutrients. Oilseed rape cultivars have high amounts of erucic acid and glucosinolate which may increase health risks. The current study was carried out in 2021 in the research area of the Department of Plant Breeding and Genetics at the University of Agriculture, Faisalabad. The goal of the experiment was to find Brassica rapa accessions with improved yield and fatty acid-related characteristics from the germplasm by screening and choosing them. One hundred accessions of B. rapa were screened for better yield and fatty acid-related traits in a randomized complete block design. Data were obtained for many morphological and fatty acid-related characteristics. Analysis of variance, mean comparison, correlation, and principal component analysis were performed on the recorded data. Three testers; 26240, 26283, and 26215 and ten lines; 28244, 40961, 40970, 40975, 40977, 40978, 40979, 40980, 40981 and 40982 were selected on a mean performance basis. The highest mean value was shown by 40975, and 40977 lines for most of the traits. The findings demonstrated that there was significant genetic variation in the oil content and mix of fatty acids across the species under study. This suggests that the oil extracted from the seeds of these lines may be appropriate for both industrial and human use. The selected accessions should be further assessed for various yield and fatty acid-related traits to modify their value for edible purposes. They may also be utilized as a favourable germplasm in the breeding program.
Keywords: Brassica rapa accessions; screening; Correlation coefficient analysis; Erucic acid; Principal component analysis